Effect of Tuina Manipulation on the Expression of Desmin in Gastrocnemius of Rats with Sciatic Nerve Injury - Xianyu FU; Junpeng ZHANG; Ziwei SONG; Jiaqi WANG; Yanan GUO; Ying MA; Juntao YAN; Shujie MA (康复学报)
Objective:To study the effect of Tuina manipulation on the gastrocnemius atrophy in rats with sciatic nerve injury.Methods:The model of sciatic nerve injury was established by repair of the outer membrane after the sciatic nerve transaction. A total of 96 male Sprague-Dawley (SD) rats were randomly divided into normal group, model group and Tuina group. The sciatic nerve was transected and the epineurium was sutured in the latter two groups. The Tuina group was given Tuina manipulation treatment once a day. Eight rats from each group were detected recovery rate of muscle wet weight to evaluate the recovery of muscular atrophy and Desmin expression to explore the mechanism of Tuina manipulation.Results:The recovery rate of muscle wet weight in the model group and the Tuina group were all ascended. Compared with the model group, the rate of the Tuina group was lower at the 4 and 8 weeks after successful modeling (P>0.05), higher at the 12 and 16 weeks after successful modeling (P<0.05). The expression of Desmin in the model group and the Tuina group showed a tendency to decrease at first, then increase and followed by decrease. The expression of Desmin in the Tuina group was higher at the 4,8,12 weeks after successful modeling (P<0.05), lower at the 16 weeks after successful modeling (P<0.05).Conclusion:Tuina can promote the recovery of gastrocnemius atrophy after sciatic nerve injury, and its mechanism may promote the differentiation and maturation of muscle satellite cells by up-regulating the expression of Desmin.